PEWARNAAN GRAF PADA PENYUSUNAN JADWAL PERKULIAHAN DI POLITEKNIK AKAMIGAS PALEMBANG - Maryana Maryana (Jurnal Teknik Patra Akademika, 2015)
Early academic semester is a problem that is quite complicated because it is always busy with a routine that should have been a solution. Schedules frequent clashes between subject with the other subject is one of several problems that occur. When viewed individually, preparation of schedules manually is not a difficult thing for their tolerance and timeline different. It will be a tricky thing if the issue involves a lot of people with a variety of activities. One of the solutions to these problems is with a graph coloring technique, where this technique will discuss the solution of problems in the preparation of class schedules by using Welch-Powell algorithm in order to obtain an optimal solution